The Use of Massive Open Online Course (MOOC) for ESL Learning: An Analysis of Learning Theories - Umiera Hashim, Haida; Md Yunus, Melor; Hashim, Harwati (International Journal of Engineering and Technology, 2018)
Massive Open Online Course (MOOC) is part of the big invention of technology in education nowadays. With the existence of technology in today’s world, technology currently acts a big role and invention in the 21st century teaching and learning. Massive Open Online Course (MOOC) is widely known by most universities all over the world. Most universities have started to implement the combination of MOOC and traditional classroom as part of the teaching and learning process especially in ESL learning. In Malaysia, English language is well-known for its role as the second language and English language is not only used in the primary and secondary level of education, but also in tertiary level of education. Thus, in relation to that, this paper intended to study students’ acceptance and perceptions on the use of Massive Open Online Course (MOOC) for ESL learning. A document analysis method is used through the secondary resources regarding MOOC and in what ways MOOC helps for ESL learning. Discussion and recommendations are further explained in this study.
Keywords: 21st Century teaching and learning; ESL learning; Massive Open Online Courses (MOOC); students’ acceptance; students’ perceptions.